Jorge Silva Melo: um percurso traçado entre linhagens e heranças - Brilhante, Maria João; Azevedo, Eunice Tudela de; Campos, Ana; Faria, Teresa (Sinais de Cena, 2017)
Jorge Silva Melo: um percurso traçado entre linhagens e heranças